2022
DOI: 10.1002/adhm.202202418
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody‐Guided Tumor‐Targeted Hollow Virus‐Like Cerium Oxide with Oxygen Self‐Supply for Intensifying Photodynamic Therapy

Abstract: The hypoxic character of tumors and the poor targeting ability of photosensitizers often limit the efficacy of photodynamic therapy (PDT). In recent years, the discovery of metal nanoenzymes and nanocarriers has improved PDT. Thereby, to improve the effective utilization of photosensitizers and oxygen (O 2 ) in tumors, herein, a nanosystem (LS-HB@HvCeO 2 -NRP1 mAb, LHCN1) is reported, in which a hollow virus-like cerium oxide (HvCeO 2 ) is surface-decorated with tumor-targeting neuropilin-1 monoclonal antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Finally, the cells were incubated shielded from light or were irradiated (655 nm laser, 100 mW cm −2 , 10 min), and then observed using CLSM. [ 22 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the cells were incubated shielded from light or were irradiated (655 nm laser, 100 mW cm −2 , 10 min), and then observed using CLSM. [ 22 ]…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the cells were incubated shielded from light or were irradiated (655 nm laser, 100 mW cm −2 , 10 min), and then observed using CLSM. [22] In Vitro Cellular Uptake: The assessment of in vitro cytotoxicity is described in the Supporting Information. Targeted imaging and cell uptake evaluations were performed based on CLSM and flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…[122] Further, it was studied that silencing of cyclophilin B (CypB) gene, peptidoglycan recognition protein impairs the insect normal growth, its structure development and transmission ability of begomoviruses. [123][124][125] This cyclophilin protein has been found in interaction with TYLCV, colocalized mainly in the midgut, eggs, and salivary glands. Moreover, this CypB protein binds with hsp70 in B. tabaci midgut that mediates the viral transmission of TYLCV.…”
Section: Virus Movement From Insect-to-plant Through Coat Protein (Cp)mentioning
confidence: 99%
“…Kim et al showed that AgNPs can be seen in the basement membrane of renal tubules in the cortical area of the kidney and also accumulate in the middle and medullary areas of the kidney (Kim et al, 2009). Numerous studies have shown that biological nanoparticles are safe (Li et al, 2023). Yahyaei et al found that the use of biological AgNPs and gold nanoparticles has no destructive effects on body tissues (Yahyaei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%